Associations of sedentary time, physical activity, and cardiorespiratory fitness with metabolic syndrome in Japanese industrial workers: The Toyota Motor Corporation Physical Activity and Fitness Study - Kaori Yagi; Tao Chen; Sanmei Chen; Masataka Suwa; Takayuki Imoto; Akira Kida; Takashi Nagami; Mitsunori Iwase; Takashi Yokochi; Shuzo Kumagai (Japanese Society of Physical Fitness and Sports Medicine, 2023)
This cross-sectional study aimed to examine the independent associations of objectively measured moderate-to-vigorous physical activity (MVPA), sedentary time (ST), and cardiorespiratory fitness (CRF) with metabolic syndrome (MetS) among industrial workers. A total of 536 Japanese male industrial workers aged 35-59 years were included in the study. MetS was defined using the 2009 Joint Interim Statement definitions. ST and MVPA were measured using a triaxial accelerometer. Maximal oxygen uptake (VO2max) was estimated through the bicycle ergometer-based submaximal aerobic fitness test. Logistic regression models were used to examine the associations of ST, MVPA, and VO2max with MetS. The mean age was 48.6 (8.1) years, and the prevalence of MetS was 12.7%. After adjusting for covariates, the odds ratios (OR) and 95% confidence intervals (CI) of prevalent MetS for the highest and middle tertiles of MVPA were 0.22 (95% CI 0.09-0.53) and 0.89 (95% CI 0.51-1.57), respectively. The OR of the prevalent MetS for the highest and middle tertiles of VO2max were 0.23 (95% CI 0.11-0.49) and 0.49 (95% CI 0.27-0.90), respectively. However, no significant association was found between ST and prevalence of MetS. The associations for MVPA and VO2max did not change materially after mutual adjustment for ST, MVPA, and/or VO2max. In conclusion, higher levels of both MVPA and CRF were independently associated with a lower likelihood of MetS among Japanese male industrial workers.